Peer effects and risk sharing in experimental asset markets - Sascha Baghestanian; Paul J. Gortner; Joël J. van der Weele (Goethe University Frankfurt, SAFE - Sustainable Architecture for Finance in Europe, 2015)
Previous research has documented strong peer effects in risk taking, but little is known about how such social influences affect market outcomes. Since the consequences of social interactions are hard to isolate in financial data, we design an experimental asset market with multiple risky assets and study how exogenous variation in real-time information about the portfolios of peer group members affects aggregate and individual risk taking. We find that peer information reduces under-diversification through changes in risk attitudes that last beyond the market environment. The effect of information depends on its framing: highlighting the highest earning trader increases willingness to take risk and average exposure in the market. Our results show that peer information is an important determinant of earnings volatility in financial markets, and we discuss implications for institutional design.
Keywords: D53; D83; G11; 330; peer effects; laboratory experiments; risk taking; asset markets